IMPROVING EMPLOYEE SATISFACTION IN HEALTH SERVICE PT ANGKASA PURA II (PERSERO) (CASE STUDY : SENTRA MEDIKA CLINIC PT ANGKASA PURA II (PERSERO)) (The Indonesian Journal of Business Administration, 2019)
Angkasa Pura II (AP2) is a company engaged in airport service, AP2 has a clinic called sentra medika clinic (SMC) to serve AP2 employees and families. During running the service at SMC, many complaints were encountered, including related to less comfortable and clean facilities at the clinic, the unclear SOP in the SMC service, the lack of responsiveness of officers and the system that was not yet running perfectly. The research aims to analyse these problems in order to provide solutions to companies in improving service quality.In analysing the problem, the writer uses qualitative data analysis (interviews) and quantitative data analysis (survey). Servqual survey with 7 (seven) dimensions is used to analyse service quality from the customer side. Analysis result of service quality is all the results of the gap are negative (the largest gap is tangible dimension, -1,23 and the lowest gap is assurance dimension, -0,92), which means the customer is not satisfied with the services provided. And for the results of the mapping of importance performance obtained 7 attributes in quadrant A, 5 attributes in quadrant B, 5 attributes in quadrant C and 8 attributes in quadrant D. Based on the results of importance and performance analysis, the attributes in quadrant A are priorities that must be immediately improved in order to get customer satisfaction.Keywords : Sentra Medika Clinic, Service Quality, Customer Satisfaction, Importance Performance Analysis (IPA), Cartesius Diagram